INTERNALISASI NILAI-NILAI RELIGIUS MELALUI PEMBIASAAN SHOLAT DHUHA DAN DZUHUR BERJAMAAH DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA SMP MUHAMMADIYAH 6 JAKARTA - Thoha, M; Fajri, Muhamad Nasrudin (Jurnal Tarbiyah Jamiat Kheir, 2025)
ABSTRACT This study aims to examine how the implementation of the Dhuha and Dhuhr congregational prayer habituation program contributes to the formation of students’ religious character at SMP Muhammadiyah 6 Jakarta. This research uses a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The research subjects were seventh and eighth-grade students, while the informants consisted of Islamic Education teachers, homeroom teachers, and the school principal. The results of the study show that the Dhuha and Dhuhr congregational prayer habituation program has been carried out routinely and systematically. Most students demonstrate active participation in these worship activities, and their religious character—such as discipline, responsibility, politeness, and social concern—has developed positively. However, it was also found that the internalization of religious values has not been fully optimal, as some students still perform worship due to external factors rather than personal awareness. Supporting factors in the success of this program include teacher role models, a religious school environment, and continuous spiritual guidance. On the other hand, obstacles encountered include students' lack of intrinsic motivation and the underutilization of value reflection after worship. It can thus be concluded that the habituation of congregational prayer has a positive influence on the formation of students’ religious character, but it should be accompanied by a deeper approach through value-based guidance, reflective mentoring, and collaboration among the school, teachers, and parents. Keywords: Dhuha Prayer, Dhuhr Congregational Prayer, Religious Character, Habituation, Islamic Education.